The Void Just Ain’t (What It Used To Be): Void, Infinity, and the Indeterminate - Chien Tho, Tzu (Filozofski vestnik, 2013)
In this paper, the author diagnoses and criticizes the use of what he calls the “atomistic strategy” in contemporary philosophy in order to understand the indeterminate and the singular. Borrowing from Antique and Hellenistic Atomism, the “atomistic strategy” makes use of the opposition between the void and atoms to theorize how transformations that are not accounted for in determinate structures arise in these very structures. As such, the void stands in as the repository of the radical and subversive negative powers that give rise to the singular indeterminate. Following the work of Alain Badiou, the author argues not only against the coherence of such a strategy, but also for an understanding of the singular indeterminate as self-grounding rather than founded on its negative relation to structure. In order to do this, he argues for the deflation of the purportedly subversive nature of the void by treating it as a stable element in structures. In doing so, he affirms the generic and subtractive character of the singular indeterminate and treats radical structural transformation as the correlate of ontological incompleteness rather than that of inconsistency.